GDNF Selectively Protects Dopamine Neurons over Serotonin Neurons Against the Neurotoxic Effects of Methamphetamine - Cass, Wayne A. (J Neurosci, 1996)
Repeated methamphetamine (METH) administration to animals can result in long-lasting decreases in striatal dopamine (DA) and serotonin (5-HT) levels. Glial cell line-derived neurotrophic factor (GDNF) has pronounced effects on dopaminergic systems in vivo, including partial neuroprotective effects against 6-hydroxydopamine and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine -induced lesions. The present study examined the ability of GDNF to prevent METH-induced reductions in potassium-evoked overflow of DA, and DA and 5-HT content, in striatum. GDNF (10 μg) or vehicle was injected into the right striatum of anesthetized rats. Twenty-four hours later, the rats were injected four times at 2 hr intervals with METH (5 mg/kg, s.c.) or saline. One week later, in vivoelectrochemistry was used to monitor the overflow of DA evoked by local potassium application. Evoked overflow of DA was dramatically decreased in the striatum of METH-treated animals. GDNF prevented the reduction in evoked overflow of DA in the right striatum of the METH-treated animals. After each experiment, the animals were killed, and striatal DA and 5-HT levels determined by HPLC. The METH treatment produced significant decreases in both neurotransmitters. GDNF administration prevented the reduction in striatal DA levels on the treated side of the brain, whereas levels on the contralateral side were still decreased. In dose–response studies, 1 μg of GDNF was as protective as 10 μg, whereas 0.1 μg was only partially protective. In contrast, 5-HT levels were only minimally protected by previous administration of GDNF. These results suggest that GDNF can selectively protect DA neurons, compared with 5-HT neurons, against the neurotoxic effects of METH.